2014
DOI: 10.1021/jp5026569
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of Cross-Linkage Structure in Boric Acid Doped Poly(vinyl alcohol) and Its Model Compound As Studied by an Organized Combination of X-ray Single-Crystal Structure Analysis, Raman Spectroscopy, and Density Functional Theoretical Calculation

Abstract: When boric acid (BA) is added to poly(vinyl alcohol) (PVA), a chemical reaction occurs to form the cross-linkages between the amorphous PVA chains. The local structural change caused by this reaction has been clarified concretely from the microscopic level on the basis of the X-ray-analyzed crystal structure, Raman spectra, and ab initio density functional theory using a model compound produced by the reaction between pentanediol (PENT) and boric acid (PENT-BA). The PENT-BA compound was found to take the TT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…The band at 932 cm −1 is assigned to the C-O stretching in polyvinyl alcohol, indicating that the degree of hydrolysis of PVAc was enhanced due to the crosslinking reaction. The increased intensity of the band at 807 cm −1 could be assigned to the newly formed borate ring including C-C bonds, as reported by Itou et al, 44 which implies that the crosslinks formed by tetra-coordinated borate ions were generated between the PVAc chains as shown in the chemical structure in Fig. 3a.…”
Section: Resultssupporting
confidence: 73%
“…The band at 932 cm −1 is assigned to the C-O stretching in polyvinyl alcohol, indicating that the degree of hydrolysis of PVAc was enhanced due to the crosslinking reaction. The increased intensity of the band at 807 cm −1 could be assigned to the newly formed borate ring including C-C bonds, as reported by Itou et al, 44 which implies that the crosslinks formed by tetra-coordinated borate ions were generated between the PVAc chains as shown in the chemical structure in Fig. 3a.…”
Section: Resultssupporting
confidence: 73%
“…The possible crosslinking structure obtained from PVA and complexes between borate ions and hydroxyl pairs of adjacent PVA chains, as shown in Figure . However, another concept of the crosslinking model between PVA and borax has been introduced . Raman results revealed that borax compounds form crosslinks between with adjacent PVA chains and this crosslinkage is reported to be temperature dependent, the number of hydrogen bonds in the PVA‐borax system decreased at high temperature and can be recovered at a low temperature …”
Section: Introductionmentioning
confidence: 99%
“…Alignment control of dichroic pigments is also important for achieving a highly achromatic polarizer with a uniform dichroic ratio in the visible wavelength range. In general, the optimum conditions for the alignment process are different for each dichroic pigment because of their different chemical structures [22][23][24][25] . The migration of dichroic pigments in the thickness direction of the film also varies depending on the chemical structure; therefore, uniform stretching of the PVA film is important for improving the alignment uniformity of dichroic pigments in the thickness direction of the film.…”
Section: Improvement Of Alignment Uniformity Of Dichroic Pigmentsmentioning
confidence: 99%